Lepidolite tailing large-dosage ultra-white body positioning crystal pattern ceramic tile and preparation method thereof
By introducing a large amount of lithium mica tail material into the ceramic body formula, and combining inkjet printing and crystal glaze-plated technology, ultra-white body and positioning crystal flower ceramic tiles were prepared, which solved the low firing temperature of lithium mica tail material ceramic tiles and the problem of poor production stability, ceramic products with high whiteness, crystallization effect and rich layering are achieved.
Patent Information
- Application Number
- CN202411226144.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-03
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-09-03
AI Technical Summary
In the prior art, when using lithium mica tail material to prepare ceramic tiles, the firing temperature is low, it is easy to foam, and it is difficult to obtain a stable high-dose ceramic body formula, which affects the performance and application range of ceramic tiles.
By introducing a large amount of lithium mica tail material into the ceramic body formula, combined with inkjet printing technology and crystal glaze throwing technology, ultra-white body and positioning crystal flower ceramic tiles are prepared, which not only achieves high whiteness and crystallization effects, but also enhances the layer richness and three-dimensionality of the ceramic tiles.
The high whiteness and stability of the ceramic blank with large amounts of lithium mica tail material was achieved, and the positioning crystal flower ceramic tiles with rich patterns and three-dimensional sense were obtained, which enhanced the aesthetics and application value of ceramic products.
Smart Images

Figure CN119504228A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of ceramic building materials, and particularly relates to an ultra-white blank positioned crystal flower ceramic tile with a large amount of lithium mica tailings added and a preparation method thereof. Background Art
[0002] The metal lithium battery industry produces a large amount of lithium mica tailings in the process of extracting lithium metal. This tailing is a waste material for the metal lithium battery industry. The amount is very large, and improper handling will cause great pollution to the environment. At present, some building ceramic companies have proposed to introduce a small amount of lithium mica tailings into ceramic blanks. Because lithium mica tailings contain a low content of metallic lithium, their firing temperature is low and they are easy to foam. Therefore, lithium mica tailings are currently commonly used to prepare foamed ceramic tiles. Moreover, the low aluminum characteristics of lithium mica tailings make it difficult to obtain a stable production formula for lithium mica tailings doped with a large amount of ceramic blanks.
[0003] The Chinese patent application number CN202211633476.X discloses a ceramic body, ceramic brick and preparation method thereof, the main formula of which is 30-65 parts of lithium mica tailings, 10-35 parts of wollastonite tailings, 10-30 parts of clay, 2-15 parts of potassium feldspar, 2-15 parts of sodium feldspar and 8-20 parts of quartz. Although the system uses a large amount of lithium mica tailings, the wollastonite formula used has a narrow firing range, poor production stability, and is prone to reversion, making it difficult to fully promote and apply it in the production line of building ceramics. Summary of the invention
[0004] In view of the above problems, the present invention provides a lithium mica tailings large amount of ultra-white body positioning crystal flower ceramic tile and a preparation method thereof, by introducing a large amount of lithium mica tailings into the ceramic body formula to prepare a ceramic body with ultra-high whiteness, and also by using inkjet printing to spread the ink to spread the lithium mica tailings large amount of ultra-white glaze, and combining the inkjet ordinary ink pattern and the lithium mica tailings large amount of crystal polishing glaze, the obtained positioning crystal flower ceramic tile has both the rich colors of inkjet printing and the crystallization effect formed according to the pattern texture, which can form a ceramic product with consistent appearance, strong three-dimensional sense and rich layers.
[0005] In the first aspect, the present invention provides a method for preparing a ceramic tile with ultra-white blank with a large amount of lithium mica tailings and positioned crystal flowers. The preparation method comprises the following steps: preparing an ultra-white blank with a large amount of lithium mica tailings; inkjet printing ink on the surface of the ultra-white blank; applying ultra-white glaze with a large amount of lithium mica tailings on the surface of the ultra-white blank after the inkjet printing and ink removal; inkjet printing a normal ink pattern on the surface of the ultra-white blank after the ultra-white glaze is applied; applying a crystal polishing glaze with a large amount of lithium mica tailings on the surface of the ultra-white blank after the normal ink pattern is inkjet printed; sintering and polishing the ultra-white blank after the crystal polishing glaze is applied to obtain a ceramic tile with ultra-white blank with a large amount of lithium mica tailings and positioned crystal flowers.
[0006] Preferably, the mineral composition of the ultra-white blank with a large amount of lithium mica tailings includes: in mass percentage, 20-45% lithium mica tailings, 8-20% ultra-white bentonite, 10-25% ultra-white ball clay, 10-30% ultra-white high-alumina sand, 2-20% albite, 2-20% potassium feldspar, and 2-5% talc.
[0007] Preferably, the chemical composition of the ultra-white blank with a large amount of lithium mica tailings includes: in mass percentage, IL: 3.0-4.5%; SiO2: 67-70%; Al2O3: 17-20%; Fe2O3: 0.15-0.4%; TiO2: ≤0.3%; CaO: 0.4-0.8%; MgO: 0.6-1.2%; K2O: 2.5-3.5%; Na2O: 1.8-2.5%.
[0008] Preferably, the mineral composition of the ultra-white glaze with a large amount of lithium mica tailings includes: in mass percentage, 30-50% lithium mica tailings, 3-15% albite, 5-15% ultra-white kaolin, 8-20% alumina, 8-18% calcined kaolin, 6-16% burned talc, 1-6% dolomite, 0.5-6% high white nepheline, and 6-10% zirconium silicate.
[0009] Preferably, the chemical composition of the ultra-white glaze with a large amount of lithium mica tailings includes, by mass percentage, IL: 1.5-3.5%; SiO2: 54-61%; Al2O3: 25-32%; Fe2O3: 0.1-0.25%; TiO2: ≤0.1%; CaO: 0.4-1.0%; MgO: 0.6-1.2%; K2O: 1.5-3.0%; Na2O: 2.5-4.0%; ZrO2: 3.5-5.5%.
[0010] Preferably, the ultra-white glaze with a large amount of lithium mica tailings is applied by spraying glaze; preferably, the specific gravity of the ultra-white glaze with a large amount of lithium mica tailings is 1.40-1.50 g / cm 3 , glaze application amount is 400~600g / m 2 .
[0011] Preferably, the mineral composition of the high-doped crystalline glaze of lithium mica tailings includes, by mass percentage, 25-45% lithium mica tailings, 3-10% ultra-white kaolin, 5-10% burned talc, 8-15% calcite, 6-16% quartz, 25-40% zinc oxide, 5-13% titanium oxide, and 4-15% low-temperature frit; wherein the chemical composition of the low-temperature frit includes, by mass percentage, SiO2: 63-69%; Al2O3: 7-11%; Fe2O3: 0.1-0.5%; TiO2: 0.1-0.5%; CaO: 8-13%; MgO: 3-5%; K2O: 0.1-0.6%; Na2O: 8-12%.
[0012] Preferably, the mineral composition of the low-temperature frit includes, by mass percentage, quartz 5-15%, albite 40-70%, dolomite 5-15%, calcite 5-15%, and talc 10-20%.
[0013] Preferably, the chemical composition of the crystal glaze with a large amount of lithium mica tailings includes, by mass percentage, IL: 7-9%; SiO2: 37-43%; Al2O3: 5-10%; Fe2O3: ≤0.25%; TiO2: 6-9%; CaO: 6-10%; MgO: 1.5-3%; K2O: 3.0-4.0%; Na2O: 1.0-2.5%; ZnO: 23-32%.
[0014] Preferably, the crystalline polishing glaze with a large amount of lithium mica tailings is applied by pouring glaze; preferably, the specific gravity of the crystalline polishing glaze with a large amount of lithium mica tailings is 1.83-1.88 g / cm 3 , glaze application amount is 450~550g / m 2 .
[0015] Preferably, the sintering temperature is 1150-1200° C., and the sintering period is 35-60 minutes.
[0016] In a second aspect, the present invention provides a ceramic tile with ultra-white blank and positioned crystal flowers with a large amount of lithium mica tailings. The ceramic tile with ultra-white blank and positioned crystal flowers with a large amount of lithium mica tailings is obtained according to the preparation method.
[0017] Beneficial Effects
[0018] The invention provides a ceramic tile with an ultra-white body and positioned crystal flowers with a large amount of lithium mica tailings added, and a preparation method thereof. A large amount of lithium mica tailings is introduced into the ceramic body formula to prepare a ceramic body with ultra-high whiteness. In addition, the ultra-white glaze with a large amount of lithium mica tailings added is spread by inkjet printing, and the ordinary ink pattern of inkjet and the crystal polishing glaze with a large amount of lithium mica tailings added are combined to obtain the positioned crystal flower ceramic tile with rich colors of inkjet printing and a crystal effect formed according to pattern textures, so as to form a ceramic product with consistent appearance, strong three-dimensional sense and rich layers. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 The layout design diagram (left) and the brick surface effect diagram (right) of the ultra-white green body positioned crystal flower ceramic tile with a large amount of lithium mica tailings prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0020] The present invention is further described by the following embodiments, which should be understood to be only used to illustrate the present invention, but not to limit the present invention. The following is an exemplary description of the preparation method of the ultra-white green body positioning crystal flower ceramic tile with a large amount of lithium mica tailings according to the present invention.
[0021] Preparation of ultra-white green bodies with large amounts of lithium mica tailings. In order to solve the problem of large amounts of lithium mica tailings produced after extracting lithium mica in the metal lithium battery industry, the present invention designs a special formula for ultra-white green bodies with large amounts of lithium mica tailings. The mineral composition of the ultra-white green bodies with large amounts of lithium mica tailings includes: in terms of mass percentage, 20-45% lithium mica tailings, 8-20% ultra-white bentonite, 10-25% ultra-white ball clay, 10-30% ultra-white high-alumina sand, 2-20% albite, 2-20% potassium feldspar, and 2-5% talc. The formula for ultra-white green bodies with large amounts of lithium mica tailings described in the present invention can simultaneously meet the requirements of whiteness, strength, and brick shape of ultra-white green bodies.
[0022] The lithium mica tailings commonly used in the lithium battery industry can be used. For example, the chemical composition of the lithium mica tailings includes: by mass percentage, IL: 0.5-2%; SiO2: 70-80%; Al2O3: 10-15%; Fe2O3: 0.1-0.5%; TiO2: 0.01-0.1%; CaO: 0.1-1%; MgO: 0.01-0.1%; K2O: 2-4%; Na2O: 3-5%; Li2O: 0.01-0.1%. As an example, the chemical composition of the lithium mica tailings used in each embodiment and comparative example includes, by mass percentage, IL: 0.81%; SiO2: 77.91%; Al2O3: 13.30%; Fe2O3: 0.12%; TiO2: 0.05%; CaO: 0.50%; MgO: 0.04%; K2O: 2.94%; Na2O: 4.28%; Li2O: 0.05%.
[0023] Weigh each raw material according to the mineral composition of the ultra-white blank with a large amount of lithium mica tailings, add water and ball mill evenly, spray powder and granulate to obtain a blank powder. As an example, an organic reinforcing agent can also be added to further improve the strength of the blank. For example, the organic reinforcing agent accounts for 0.2 to 1.0% of the total mass of the mineral composition of the ultra-white blank with a large amount of lithium mica tailings. The blank powder is molded to obtain an ultra-white blank with a large amount of lithium mica tailings. The molding method includes but is not limited to extrusion molding and / or compression molding. In some embodiments, the whiteness of the ultra-white blank with a large amount of lithium mica tailings can be 58 to 60 degrees.
[0024] In some embodiments, the chemical composition of the ultra-white blank with a large amount of lithium mica tailings includes: in mass percentage, IL: 3.0-4.5%; SiO2: 67-70%; Al2O3: 17-20%; Fe2O3: 0.15-0.4%; TiO2: ≤0.3% (for example, 0.01-0.3%); CaO: 0.4-0.8%; MgO: 0.6-1.2%; K2O: 2.5-3.5%; Na2O: 1.8-2.5%.
[0025] The ultra-white green body with a large amount of lithium mica tailings is dried. The green body can be polished after drying. In this way, a green body with a dense, smooth and flat surface is obtained. The temperature of the green body can be controlled at 35-50°C. As an example, the strength of the dried green body is 2.2-2.5MPa.
[0026] The ink is printed by inkjet on the surface of the ultra-white blank with a large amount of lithium mica tailings. The composition of the ink is not the innovation of the present invention. Commercial ink can be used. For example, the Fluke brand ink is used in each embodiment and comparative example. The ink can be printed by inkjet according to the layout design.
[0027] A super white glaze with a large amount of lithium mica tailings is applied to the surface of the super white blank after the ink is pushed away by inkjet printing. The super white glaze is spread out at the position where the ink is pushed away by inkjet printing to form a line texture with a concave and convex three-dimensional sense. The mineral composition of the super white glaze with a large amount of lithium mica tailings includes: in terms of mass percentage, 30-50% of lithium mica tailings, 3-15% of albite, 5-15% of super white kaolin, 8-20% of alumina, 8-18% of calcined kaolin, 6-16% of burned talc, 1-6% of dolomite, 0.5-6% of high white nepheline, and 6-10% of zirconium silicate.
[0028] In some embodiments, the chemical composition of the ultra-white glaze with a large amount of lithium mica tailings includes: in mass percentage, IL: 1.5-3.5%; SiO2: 54-61%; Al2O3: 25-32%; Fe2O3: 0.1-0.25%; TiO2: ≤0.1% (for example, 0.01-0.1%); CaO: 0.4-1.0%; MgO: 0.6-1.2%; K2O: 1.5-3.0%; Na2O: 2.5-4.0%; ZrSiO4: 3.5-5.5%.
[0029] The application method of the lithium mica tailings high-doped ultra-white glaze can be spraying. In some embodiments, the specific gravity of the lithium mica tailings high-doped ultra-white glaze is 1.40-1.50 g / cm 3 , glaze application amount is 400~600g / m 2 . If the amount of ultra-white glaze with a large amount of lithium mica tailings applied is too low, the base color and defects of the body cannot be covered, resulting in a dark base color, blurred pattern layering effect, and poor combination of crystal flowers and pattern textures. If the amount of ultra-white glaze with a large amount of lithium mica tailings applied is too high, the moisture content of the body will be high, drainage will be difficult during firing, bricks will be easily blown up, and it will be unfavorable for production. When preparing the glaze slurry of ultra-white glaze with a large amount of lithium mica tailings, additives and water can be added to the mineral composition of the ultra-white glaze with a large amount of lithium mica tailings, ball milled evenly, sieved, and the glaze slurry is obtained. The additives include but are not limited to sodium carboxymethyl cellulose and sodium tripolyphosphate. The sieve residue of the glaze slurry passing through a 325 mesh sieve can be within 0.5wt%. When used, water can be added to the glaze slurry to obtain the final required glaze slurry specific gravity.
[0030] The ordinary ink pattern is inkjet printed on the surface of the ultra-white body after the ultra-white top glaze is applied. The texture and color of the inkjet printed ordinary ink pattern can be adjusted according to the layout design.
[0031] Crystallized glaze with a large amount of lithium mica tailings is applied on the surface of the ultra-white blank after inkjet printing of ordinary ink patterns.
[0032] The mineral composition of the crystallization glaze with a large amount of lithium mica tailings includes: by mass percentage, 25-45% lithium mica tailings, 3-10% ultra-white kaolin, 5-10% burned talc, 8-15% calcite, 6-16% quartz, 25-40% zinc oxide, 5-13% titanium oxide, and 4-15% low-temperature frit. The function of the low-temperature frit is to reduce the temperature of the crystallization glaze and promote the formation of crystal nuclei. If the low-temperature frit is omitted in the crystallization glaze, the crystallization effect will be poor and the crystal flowers will become smaller. In addition, the lithium mica tailings contain a small amount of lithium, which is conducive to reducing the initial melting temperature of the crystallization glaze and promoting the formation of crystals.
[0033] Among them, the chemical composition of the low-temperature melt includes: in terms of mass percentage, SiO2: 63-69%; Al2O3: 7-11%; Fe2O3: 0.1-0.5%; TiO2: 0.1-0.5%; CaO: 8-13%; MgO: 3-5%; K2O: 0.1-0.6%; Na2O: 8-12%.
[0034] As an example, the mineral composition of the low-temperature frit includes: by mass percentage, quartz 5-15%, albite 40-70%, dolomite 5-15%, calcite 5-15%, talc 10-20%. According to the mineral composition of the low-temperature frit, each raw material is weighed, mixed evenly, melted at 1550-1580°C for 12-14 hours, and then water quenched and crushed to obtain the low-temperature frit.
[0035] In some embodiments, the chemical composition of the crystal glaze with a large amount of lithium mica tailings includes: in mass percentage, IL: 7-9%; SiO2: 37-43%; Al2O3: 5-10%; Fe2O3: ≤0.25% (preferably 0.01-0.25%); TiO2: 6-9%; CaO: 6-10%; MgO: 1.5-3%; K2O: 3.0-4.0%; Na2O: 1.0-2.5%; ZnO: 23-32%.
[0036] The crystalline glaze with a large amount of lithium mica tailings can be applied by pouring glaze. In some embodiments, the specific gravity of the crystalline glaze with a large amount of lithium mica tailings is 1.83-1.88 g / cm 3 , glaze application amount is 450~550g / m 2 . If the amount of the crystallized polished glaze with a large amount of lithium mica tailings applied is too low, it will result in the failure to form crystal flowers or the crystal flowers will be small in size. If the amount of the crystallized polished glaze with a large amount of lithium mica tailings applied is too high, it will result in poor glaze transparency, poor air exhaust, and many pores. When preparing the glaze slurry of the crystallized polished glaze with a large amount of lithium mica tailings, additives and water can be added to the mineral composition of the crystallized polished glaze with a large amount of lithium mica tailings, ball milling can be carried out evenly, and sieved to obtain the crystallized polished glaze slurry. The additives include but are not limited to sodium carboxymethyl cellulose and sodium tripolyphosphate. The residue of the crystallized polished glaze slurry passing through a 325 mesh sieve can be within 0.5wt%. When in use, water can be added to the crystallized polished glaze slurry to obtain the final required glaze slurry specific gravity.
[0037] The green body after applying the crystallization glaze with a large amount of lithium mica tail material is fired and polished to form a tile with a crystallization effect. In some embodiments, the firing temperature is 1150-1200° C., and the firing cycle is 35-60 minutes. For example, the firing temperature is 1160-1170° C., and the firing cycle is 45-50 minutes.
[0038] In summary, the present invention introduces a large amount of lithium mica tailings into the ceramic formula and glaze formula to solve the problem of tailings treatment generated after lithium mica is extracted in the lithium battery industry, improves the whiteness of the ceramic body, and after inkjet printing, the ultra-white glaze is positioned and removed, combined with inkjet patterns and crystallized glaze, and the obtained ceramic tile glaze has a good sense of transparency, with both rich pattern decoration of inkjet printing and positioning crystallization effect of matching pattern texture (positioned crystallization means that the surface glaze is removed at the position where the ink is removed by inkjet printing, so that the crystallized glaze layer at the position where the ink is removed is thicker, which is more conducive to crystallization). The water absorption rate of the ultra-white body positioning crystal flower ceramic tile with a large amount of lithium mica tailings can be controlled within 0.5wt%.
[0039] The following examples are further listed to illustrate the present invention in detail. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention belong to the scope of protection of the present invention. The specific process parameters and the like in the following examples are also only examples within a suitable range, that is, those skilled in the art can make a selection within a suitable range through the description herein, and are not limited to the specific values exemplified below.
[0040] Example 1
[0041] The preparation method of ultra-white green body positioning crystal flower ceramic tile with large amount of lithium mica tail material comprises the following steps:
[0042] Step 1. Prepare a super white body with a large amount of lithium mica tailings. The mineral composition of the super white body with a large amount of lithium mica tailings includes: by mass percentage, 35% lithium mica tailings, 14% super white bentonite, 18% super white ball clay, 15% super white high alumina sand, 10% albite, 4% potassium feldspar, and 4% talc. The chemical composition of the super white body with a large amount of lithium mica tailings includes: by mass percentage, IL: 4.07%; SiO2: 69.85%; Al2O3: 18.65%; Fe2O3: 0.2%; TiO2: 0.12%; CaO: 0.66%; MgO: 0.95%; K2O: 3.25%; Na2O: 2.25%.
[0043] Step 2: inkjet printing and spreading ink on the surface of the ultra-white body with a large amount of lithium mica tailings according to the pattern design.
[0044] Step 3. Apply a high-volume ultra-white glaze of lithium mica tailings on the surface of the ultra-white blank after the ink is removed by inkjet printing. The mineral composition of the ultra-white glaze of lithium mica tailings includes: by mass percentage, 40% lithium mica tailings, 10% albite, 8% ultra-white kaolin, 13% alumina, 8% calcined kaolin, 8% burned talc, 2% dolomite, 3% high white nepheline, and 8% zirconium silicate. The chemical composition of the ultra-white glaze of lithium mica tailings includes: by mass percentage, IL: 2.0%; SiO2: 55.5%; Al2O3: 29.2%; Fe2O3: 0.12%; TiO2: 0.08%; CaO: 0.75%; MgO: 1.05%; K2O: 2.8%; Na2O: 3.7%; ZrO2: 4.8%. The application method of the ultra-white glaze with a large amount of lithium mica tailings is spraying. The specific gravity of the ultra-white glaze with a large amount of lithium mica tailings is 1.40g / cm 3 , glaze application amount is 500g / m 2 .
[0045] Step 4. Inkjet printing a normal ink pattern on the surface of the ultra-white body after applying ultra-white glaze with a large amount of lithium mica tailings.
[0046] Step 5. Apply a large amount of crystalline glaze of lithium mica tailings to the surface of the blank after the inkjet printing of the ordinary ink pattern. The mineral composition of the crystalline glaze of lithium mica tailings includes: by mass percentage, 28% of lithium mica tailings, 4% of ultra-white kaolin, 6% of burned talc, 12% of calcite, 6% of quartz, 30% of zinc oxide, 9% of titanium oxide, and 5% of low-temperature frit. The chemical composition of the low-temperature frit includes: by mass percentage, IL: SiO2: 66.76%; Al2O3: 7.84%; Fe2O3: 0.42%; TiO2: 0.13%; CaO: 10.48%; MgO: 3.84%; K2O: 0.47%; Na2O: 10.06%. The chemical composition of the crystalline glaze with a large amount of lithium mica tailings includes: in terms of mass percentage, IL: 7.28%; SiO2: 40.59%; Al2O3: 6.14%; Fe2O3: 0.15%; TiO2: 7.70%; CaO: 6.28%; MgO: 1.88%; K2O: 3.23%; Na2O: 1.38%; ZnO: 25.37%. The crystalline glaze with a large amount of lithium mica tailings is applied by pouring glaze. The specific gravity of the crystalline glaze with a large amount of lithium mica tailings is 1.88g / cm 3 , application amount is 550g / m 2 .
[0047] Step 6. The green body with a large amount of lithium mica tailings added to the crystal glaze is fired and polished to form a crystal flower ceramic tile with a large amount of lithium mica tailings added to the green body. The firing temperature is 1170° C. and the firing cycle is 50 minutes.
[0048] from Figure 1 It can be seen that the surface of the ultra-white green body positioned crystal flower ceramic tile product with a large amount of lithium mica tailings prepared in this embodiment has a crystal flower effect consistent with the layout design.
[0049] Comparative Example 1
[0050] The invention is basically the same as Example 1, except that the ultra-white body with a large amount of lithium mica tailings is replaced by a wollastonite system body. The mineral composition of the wollastonite system body includes, by mass percentage, 30% of lithium mica tailings, 15% of ultra-white bentonite, 18% of ultra-white ball clay, 10% of quartz, 4% of albite, 8% of potassium feldspar, and 15% of wollastonite.
[0051] During the production process, it was found that the comparative example 1 used a wollastonite-based body, which had unstable water absorption and was prone to reversion (i.e., secondary deformation leading to deterioration of the brick shape), ultimately causing unstable brick shape.
[0052] Comparative Example 2
[0053] The invention is basically the same as Example 1, and the only difference is that the ultra-white glaze with a large amount of lithium mica tailings is replaced by an ultra-white glaze with a low amount of lithium mica tailings. The mineral composition of the ultra-white glaze with a low amount of lithium mica tailings includes: by mass percentage, 5% of lithium mica tailings, 19% of albite, 20% of potassium feldspar, 5% of quartz, 2% of wollastonite, 8% of ultra-white kaolin, 12% of alumina, 10% of calcined kaolin, 7% of burned talc, 1% of dolomite, 3% of high white nepheline, and 8% of zirconium silicate.
[0054] The formula of the ultra-white glaze with low content of lithium mica tailings in comparative example 2 does not match that of the ultra-white body with high content of lithium mica tailings, resulting in excessive differences in the initial melting temperature and expansion properties, causing the brick to distort and resulting in a large brick shape deviation.
[0055] Comparative Example 3
[0056] The invention is basically the same as Example 1, and the only difference is that the crystalline glaze with a large amount of lithium mica tailings is replaced by a conventional glaze with a large amount of lithium mica tailings. The mineral composition of the conventional glaze with a large amount of lithium mica tailings includes: by mass percentage, 30% of lithium mica tailings, 4% of ultra-white kaolin, 8% of burned talc, 10% of calcite, 14% of quartz, 3% of zinc oxide, 7% of strontium carbonate, 10% of potassium feldspar, and 14% of sodium feldspar.
[0057] The glaze polishing of comparative example 3 has no crystallization effect and has poor glaze quality, and is prone to defects such as holes.
[0058] Comparative Example 4
[0059] The invention is basically the same as Example 1, except that the ultra-white glaze with a large amount of lithium mica tailings is replaced by a seepage glaze. The mineral composition of the seepage glaze includes, by mass percentage, 30% potassium feldspar, 20% sodium feldspar, 8.5% quartz, 8% kaolin, 3% burned talc, 27% lithium mica tailings, and 3.5% nano color enhancer.
[0060] This comparative example 4 uses a seepage glaze. Since the seepage glaze diffuses unevenly in the brick, it is difficult to control the seepage depth, which affects the pattern clarity and reduces the pattern texture level.
Claims
1. A method for preparing ultra-white green body positioning crystal flower ceramic tiles with a large amount of lithium mica tailings, characterized in that: The preparation method comprises the following steps: Preparation of ultra-white green bodies with large amounts of lithium mica tailings; Inkjet printing and spreading ink on the surface of the ultra-white blank; Applying ultra-white glaze with a large amount of lithium mica tailings on the surface of the ultra-white blank after the ink is removed by inkjet printing; inkjet printing a common ink pattern on the surface of the ultra-white body after the ultra-white glaze is applied; Applying a large amount of crystalline glaze of lithium mica tailings on the surface of the ultra-white blank after the ordinary ink pattern is inkjet printed; The ultra-white body after the crystal glaze is applied is fired and polished to obtain ultra-white body positioning crystal flower ceramic tiles with a large amount of lithium mica tail material.
2. The preparation method according to claim 1, characterized in that: The mineral composition of the ultra-white blank with a large amount of lithium mica tailings includes: in percentage by mass, 20-45% of lithium mica tailings, 8-20% of ultra-white bentonite, 10-25% of ultra-white ball clay, 10-30% of ultra-white high-alumina sand, 2-20% of albite, 2-20% of potassium feldspar, and 2-5% of talc.
3. The preparation method according to claim 1 or 2, characterized in that: The chemical composition of the ultra-white blank with a large amount of lithium mica tail material includes, by mass percentage, IL: 3.0-4.5%; SiO2: 67-70%; Al2O3: 17-20%; Fe2O3: 0.15-0.4%; TiO2: ≤0.3%; CaO: 0.4-0.8%; MgO: 0.6-1.2%; K2O: 2.5-3.5%; Na2O: 1.8-2.5%.
4. The preparation method according to any one of claims 1 to 3, characterized in that The mineral composition of the ultra-white glaze with a large amount of lithium mica tailings includes: in mass percentage, 30-50% of lithium mica tailings, 3-15% of albite, 5-15% of ultra-white kaolin, 8-20% of aluminum oxide, 8-18% of calcined kaolin, 6-16% of burned talc, 1-6% of dolomite, 0.5-6% of high white nepheline, and 6-10% of zirconium silicate.
5. The preparation method according to any one of claims 1 to 4, characterized in that: The chemical composition of the ultra-white glaze with a large amount of lithium mica tailings includes, by mass percentage, IL: 1.5-3.5%; SiO2: 54-61%; Al2O3: 25-32%; Fe2O3: 0.1-0.25%; TiO2: ≤0.1%; CaO: 0.4-1.0%; MgO: 0.6-1.2%; K2O: 1.5-3.0%; Na2O: 2.5-4.0%; ZrO2: 3.5-5.5%.
6. The preparation method according to any one of claims 1 to 5, characterized in that The application method of the ultra-white glaze with a large amount of lithium mica tailings is spraying glaze; preferably, the specific gravity of the ultra-white glaze with a large amount of lithium mica tailings is 1.40-1.50 g / cm 3 , glaze application amount is 400~600g / m 2 .
7. The preparation method according to any one of claims 1 to 6, characterized in that The mineral composition of the crystal glaze with a large amount of lithium mica tailings includes, by mass percentage, 25-45% lithium mica tailings, 3-10% ultra-white kaolin, 5-10% burned talc, 8-15% calcite, 6-16% quartz, 25-40% zinc oxide, 5-13% titanium oxide, and 4-15% low-temperature frit; wherein the chemical composition of the low-temperature frit includes, by mass percentage, SiO2: 63-69%; Al2O3: 7-11%; Fe2O3: 0.1-0.5%; TiO2: 0.1-0.5%; CaO: 8-13%; MgO: 3-5%; K2O: 0.1-0.6%; Na2O: 8-12%.
8. The preparation method according to claim 7, characterized in that: The mineral composition of the low-temperature frit includes, by mass percentage, quartz 5-15%, albite 40-70%, dolomite 5-15%, calcite 5-15%, and talc 10-20%.
9. The preparation method according to any one of claims 1 to 8, characterized in that: The chemical composition of the crystallized glaze with a large amount of lithium mica tail material includes, by mass percentage, IL: 7-9%; SiO2: 37-43%; Al2O3: 5-10%; Fe2O3: ≤0.25%; TiO2: 6-9%; CaO: 6-10%; MgO: 1.5-3%; K2O: 3.0-4.0%; Na2O: 1.0-2.5%; ZnO: 23-32%.
10. The preparation method according to any one of claims 1 to 9, characterized in that: The crystalline polishing glaze with a large amount of lithium mica tailings is applied by pouring glaze; preferably, the specific gravity of the crystalline polishing glaze with a large amount of lithium mica tailings is 1.83-1.88 g / cm 3 , glaze application amount is 450~550g / m 2 .
11. The preparation method according to any one of claims 1 to 10, characterized in that: The sintering temperature is 1150-1200° C., and the sintering period is 35-60 minutes.
12. A super white green body positioning crystal flower ceramic tile with a large amount of lithium mica tailings, characterized in that: The ultra-white green body positioned crystal flower ceramic tile with a large amount of lithium mica tailings is obtained by the preparation method described in any one of claims 1 to 11.
Citation Information
Patent Citations
Ceramic inkjet penetrated overglaze containing lepidolite tailings
CN107032612A
Ceramic green body, ceramic tile and preparation method of ceramic green body
CN115893978A
Easy-to-clean domestic ceramic and preparation method thereof
CN117362021A
Method for preparing ecological foamed ceramic from lepidolite filter mud whole waste
US20240059619A1